Influence of Organizational Culture on Work Engagement among Generation X and Y in Bosnia and Herzegvina and Turkey - Kozo, Amra (My University, 2017)
Muhtemelen çoğu kişi Rice ve arkadaşlarının (2012:104) “kültürsüz örgüt diye bir şey yoktur” sözü ile aynı fikirdedir. ABSTRACT Probably many would agree with Rice et al. (2012: 104) that „there is no such a thing as a culture-less organization.“
Keywords: Generation X; Generation Y; Generational Cohorts; İş Bağlılığı; İşletme; Nesil Kohortları; Örgüt kültürü; Örgütsel davranış; Work Engagement; X Kuşağı; Y Kuşağı Organizational Culture; Yönetim ve organizasyon